Conquering Post-Dural Puncture Headache: A Systematic Review of Effective Treatments - Kopczyński, Cezary; Kopczyńska, Urszula; Malinowski, Piotr; Sikorski, Piotr; Gurdak, Kinga; Dydyk, Martyna; Dyrek, Martyna; Błaszczak, Ewa; Wójcik, Jakub; Partyka, Aleksandra (Journal of Education, Health and Sport, 2024)
Post-dural puncture headache (PDPH) is a common complication following spinal procedures, particularly lumbar punctures and epidural anesthesia. This systematic review aims to evaluate and compare the effectiveness of various management strategies for PDPH. A comprehensive search was conducted across major databases for relevant articles published up to January 2024. The inclusion criteria comprised studies assessing interventions for post-dural puncture headache (PDPH) management in adult populations. Data extraction and quality evaluation were conducted independently by two reviewers. Analysis involved 34 studies meeting the inclusion criteria. The results indicate that conservative approaches, including bed rest, hydration, caffeine, and analgesics, continue to serve as the fundamental components of PDPH management. Additionally, epidural blood patch (EBP) emerged as the most effective intervention for refractory cases. However, further research is needed to optimize treatment protocols and explore emerging therapies.